Temporal trend of inactive commuting to school in adolescents from Sergipe, Brazil - Santos, Lucas Souza; Ribeiro, Davi Soares Santos; Barreto, Íkaro Daniel Carvalho; Oliveira, Vítor Hugo Fernandes de; Silva, Danilo Rodrigues Pereira da; Menezes, Aldemir Smith (Scientia Plena, 2020)
Our purpose was to identify the trend of inactive commuting to school and to verify the associated factors (demographic, socioeconomic, school and environmental) to this outcome. The study compared data from two cross-sectional epidemiological surveys with samples of 3,984 (in 2011) and 4,139 (in 2016) adolescents from public schools of Sergipe, Brazil. Inactive commuting comprised the adolescents who did not walk or cycle to school on any day of the week. Raw and adjusted logistic regression were used to analyze the association between independent variables and outcome. The findings revealed that, in 2011, there was observed a greater probability of inactive commuting among students from the urban area (OR=3.91; 95% CI=3.37-4.45), enrolled in the day shift (OR=1.20; 95% CI=1.04-1.40), with a family income of up to one minimum wage (OR=1.39; 95% CI=1.15-1.68) and between one and two minimum wages (OR=1.20; 95% CI=1, 00-1.43), which took up to 29 minutes (OR=1.82; 95% CI=1.47-2.25) and 30 to 59 minutes when commuting from home to school (OR=1.73; 95% CI=1.36-2.21). In 2016, male adolescents (OR=1.18; 95% CI=1.03-1.36), living in the urban area (OR=3.78; 95% CI=3.23-4.41), living on paved streets (OR=1.18; 95% CI=1.00 -1.39), which took up to 29 minutes (OR=2.24; 95% CI=1.82-2.77) and 30 to 59 minutes when commuting (OR=1.35; 95% CI=1.05-1.72) showed higher prevalence of inactive commuting to school. Some socioeconomic and demographic factors influenced the stability of the high prevalence of inactive commuting to school.